1990
DOI: 10.3758/bf03211584
|View full text |Cite
|
Sign up to set email alerts
|

Does stimulus context affect loudness or only loudness judgments?

Abstract: Marks (1988) reported that when equal-loudness matches were inferred from magnitude estimates of loudness for tones of two different frequencies, the matches were affected by changes in the stimulus intensity range at both frequencies. Marks interpreted these results as reflecting the operation of response biases in the subjects' estimates; that is, the effect of range was to alter subjects' judgments but not necessarily the perception ofloudness itself. We investigated this effect by having subjects choose wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
79
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 27 publications
6
79
0
Order By: Relevance
“…The present results show that the shifts in NaCI-sucrose matches reported by Rankin and Marks (1991) are not due to different response output functions for NaCI and sucrose,but result from contextdependent internal representations. Schneider and Parker (1990) and Marks (1992) reached a similar conclusion employing auditory stimuli in nonnumerical judgment tasks.…”
Section: Discussionsupporting
confidence: 59%
“…The present results show that the shifts in NaCI-sucrose matches reported by Rankin and Marks (1991) are not due to different response output functions for NaCI and sucrose,but result from contextdependent internal representations. Schneider and Parker (1990) and Marks (1992) reached a similar conclusion employing auditory stimuli in nonnumerical judgment tasks.…”
Section: Discussionsupporting
confidence: 59%
“…It therefore seems that the effects of a particular manipulation depend upon the other items that are presented for judgement during the session. This kind of context effect is common in studies of perceptual discrimination and identification in both humans and animals (e.g., Hinson & Lockhead, 1986;Matthews & Stewart, 2008;Schneider & Parker, 1990), and the present results emphasize that any conclusions drawn from the verbal estimation procedure are conditional upon the specific experimental context: manipulations do not have absolute effects on the switch latencies or pacemaker rate of an internal clock. Rather, these effects depend upon the other items included in the session.…”
Section: Discussionsupporting
confidence: 54%
“…In these studies, stimuli that have been drawn from two different distributions are presented in the same experimental setting. To the extent that these studies demonstrate a contextual effect of the different distributions, they appear to demonstrate contrast rather than assimilation effects (Marks, 1988(Marks, , 1992Schneider & Parker, 1990;Wedell, 1995). For example, Marks (1988) found that magnitude estimates of the loudness of a 2500-Hz tone were greater than those of the loudness of a 500-Hz tone of the same amplitude when the set of 2500-Hz tones was generally softer than the set of 500-Hz tones.…”
mentioning
confidence: 89%